How to treat benchmark revisions? The case of German production and orders statistics - Thomas A. Knetsch; Hans-Eggert Reimers (Deutsche Bundesbank, 2006)
Elements of an econometric examination of benchmark revisions in real-time data are suggested. Structural break tests may be applied to detect heterogeneities within vintages. Systems cointegration tests are helpful to reveal inconsistencies across vintages. Differencing and rebasing, often used to adjust for benchmark revisions, are generally not sufficient to ensure consistent real-time macroeconomic data. Vintage transformation functions estimated by cointegrating regressions are more flexible. Inappropriate conversion may cause observed revision statistics to be affected by nuisance parameters. In German industrial production and orders statistics, remaining revisions are generally biased and serially correlated.
Keywords: C82; C32; C22; 330; real-time data; benchmark revisions; industrial production; orders; Statistische Methode; Produktionsstatistik; Auftrag; Indexberechnung; Zeitreihenanalyse; Theorie; Deutschland